“Reverse combustion” of carbon dioxide in water: The influence of reaction conditions - Quintana-Gómez, Laura; Connolly, Matthew; Shehab, Amal K.; Al-Shathr, Ali; McGregor, James (Frontiers in Energy Research, 2022)
The synthesis of value-added organic products from the hydrothermal conversion of CO2 and H2O has been demonstrated, revealing the impact that reaction conditions have on the product distribution and yield. CO2 has the potential to become a valuable feedstock for the chemicals sector, in part displacing fossil resources and improving the economics of carbon capture. Herein the conversion of CO2 with H2O, in the absence of gas-phase H2, to methanol and other products is shown to occur under sub-critical water conditions in the presence of iron as a reductant and catalyst: this process can be considered as a form of “reverse combustion”. The influence of reaction temperature between 200-350 °C and CO2:O2 mole ratio from 9-119 (in addition to pure 100% CO2) have been investigated in the presence of Fe powder. The influence of reaction time has also been investigated, employing Fe3O4 as a catalyst. Product analysis is conducted by GC-MS and MS for liquid- and gas-phase products respectively, while SEM and XRD are employed to analyse morphological changes in the catalyst and TPO investigates any coke deposited during reaction. Methanol is the major product formed at all conditions investigated, with a maximum concentration of 8 mmol L 1 after 12 h of reaction, or after 4 h in the presence of oxygen. Acetone and ethanol are also formed, although in smaller quantities than methanol, with larger-chained species also present. An inverse relationship is observed between acetone and ethanol concentrations. Based on the analysis of the reaction data it is hypothesized that ethanol and acetone may be competitively produced in one reaction pathway, while methanol is produced in an independent, parallel, pathway. The observation of acetaldehyde in the gas-phase at all studied conditions suggests that acetone may be produced from the dehydrogenation of ethanol via an acetaldehyde intermediate; catalyzed by zero-valent iron sites. Morphological characterization indicates that the catalysts are stable under the reaction conditions. These studies facilitate the development of improved catalysts and processes for the hydrothermal conversion of CO2, allowing further development of this promising sustainable process.